Characterization of nanostructured CdTe synthesized by solid state microwave-plasma process - Promnopas W. (2014)
Purified cubic CdTe nanocrystals were synthesized from 1:1 molar ratio of Cd:Te using 900 W microwave plasma. The phase was detected using X-ray diffraction (XRD), which are in accordance with those of the simulation, and selected area electron diffraction (SAED). Raman spectroscopic, scanning electron microscopic (SEM) and focused ion beam (FIB) techniques showed that the products were nanocrystals with fundamental transverse optical (1TO) and longitudinal optical (1LO) vibrations at 140 cm-1 and 169 cm-1, respectively. Its direct energy gap (Eg) was determined to be 1. 6 eV.